2021
DOI: 10.26434/chemrxiv-2021-n0d4x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Soft-Solid Co-Crystalline Electrolyte Combining Advantages of Organics and Ceramics: Thermally, Electrochemically Stable, Highly Conductive (Adiponitrile)2LiPF6

Abstract: The solid electrolyte (ADN)2LiPF6 is described. The structure exhibits adiponitrile (ADN)-based channels based on XRD analysis, through which the -C≡N-solvated Li+ ions migrate. High conductivity (σ ~ 10-4 S/cm) and high lithium ion transference number (tLi+ = 0.54) results from weak interactions between “hard” (charge-dense) Li+ ions and “soft” (electronically polarizable) -C≡N, compared with the stronger interactions of previously reported “hard” ether oxygen contacts of polyethylene oxide (PEO) or glymes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In another work, a similar solvent-assisted migration of the Li + ion has also been observed, where the cyano group on adiponitrile supports the migration of Li + ions to an occupancy site at a distance of >0.6 nm, without any interference from anions. 28 Despite having a close agreement for E a,exp and E a,DFT for (DMF) 3 NaClO 4 , poor agreement with E a from MD simulations was still an unsolved question. We hypothesized that the MD simulations at and above room temperature do not exclusively manifest just the Na + ion conduction in (DMF) 3 NaClO 4 because the simulations have also shown that around room temperature the crystals form a dynamic equilibrium with 2:1 stoichiometry as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, a similar solvent-assisted migration of the Li + ion has also been observed, where the cyano group on adiponitrile supports the migration of Li + ions to an occupancy site at a distance of >0.6 nm, without any interference from anions. 28 Despite having a close agreement for E a,exp and E a,DFT for (DMF) 3 NaClO 4 , poor agreement with E a from MD simulations was still an unsolved question. We hypothesized that the MD simulations at and above room temperature do not exclusively manifest just the Na + ion conduction in (DMF) 3 NaClO 4 because the simulations have also shown that around room temperature the crystals form a dynamic equilibrium with 2:1 stoichiometry as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We also described that these crystals and others like them exhibit a nanoliquid surface layer resulting from the decreased lattice energy at the surface, which we have detected experimentally (SEM) and described using MD simulations on several materials. 28,29 This surface nanoliquid layer at the grain boundaries naturally binds grains to one another and facilitates ion conduction across electrolyte particles, circumventing the grain-boundary problem common to other solid electrolyte systems. Apart from these peculiar structural properties, these cocrystals exhibit a conductivity of 3 × 10 −4 S cm −1 with an E a barrier of 25 kJ mol −1 for Na + ion conduction calculated from temperature-dependent impedance spectroscopy measurements.…”
Section: ■ Introductionmentioning
confidence: 99%